2023
DOI: 10.1007/s12035-023-03777-y
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Promotes Pro/anti-inflammatory Phenotypic Transformation of Microglia via Wnt/β-catenin Pathway in Hypoxic-Ischemic Neonatal Rats

Luting Yu,
Lingyi Huang,
Yuanyuan Zhao
et al.

Abstract: Inflammatory reaction plays a key role in the pathogenesis of hypoxic-ischemic encephalopathy (HIE) in neonates. Microglia are resident innate immune cells in the central nervous system and are profoundly involved in neuroinflammation. Studies have revealed that atorvastatin exerts a neuroprotective effect by regulating neuroinflammation in adult animal models of brain stroke and traumatic brain injury, but its role regarding damage to the developing brain remains unclear. This study aimed to clarify the effec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Based on our data, we cannot exclude the possibility that complement-activated microglia promote pathological inflammation, because activated microglia have the ability to induce cell death and increase inflammatory responses ( 64 , 81 ), which may in turn lead to brain tissue damage and infiltration in TBM. Furthermore, our proposed temporal trajectory analysis of myeloid cells indicated that Macro_C01 cells were in a terminal differentiation state in the CSF compared to other myeloid cells, potentially implying that they originate from a distinct differentiation pathway.…”
Section: Discussionmentioning
confidence: 90%
“…Based on our data, we cannot exclude the possibility that complement-activated microglia promote pathological inflammation, because activated microglia have the ability to induce cell death and increase inflammatory responses ( 64 , 81 ), which may in turn lead to brain tissue damage and infiltration in TBM. Furthermore, our proposed temporal trajectory analysis of myeloid cells indicated that Macro_C01 cells were in a terminal differentiation state in the CSF compared to other myeloid cells, potentially implying that they originate from a distinct differentiation pathway.…”
Section: Discussionmentioning
confidence: 90%